A type curve approach to qualitative description of reservoir fluids (1993)
Qualitative description of reservoir fluids is normally based on such parameters as saturation pressure, gas in solution, viscosity and density. Most Engineers ignore compositional data unless when phase behavior predictions or compositional simulation are to be undertaken. This work describes a simple, quick method of qualitative reservoir crude assessment, using the well known Type Curve matching techniques with fluid compositional data. The method is demonstrated for some Niger Delta reservoir crudes, and shown to be useful in checking the validity of laboratory PVT results in cases where there are disagreements between the experimental and observed (field) values of saturation pressure. Volatile crudes and condensates can also he readily identified. It. would appear that the method can be applied regionally, as well as locally (in-field) as an aid in reservoir-to-reservoir fluid correlation. It can also help to ide1ltify non-equilibrium fluid distribution in. large, thick, or segmented reservoirs.